Cover Image. Issue 28 (21st September 2022) - Baba, Hiromi; Urano, Ryo; Nagai, Tetsuro; Okazaki, Susumu
Abstract : The cover image is based on the Research Article Prediction of self‐diffusion coefficients of chemically diverse pure liquids by all‐atom molecular dynamics simulations by Hiromi Baba et al., https://doi.org/10.1002/jcc.26975 Abstract : The cover image is based on the Research Article Prediction of self‐diffusion coefficients of chemically diverse pure liquids by all‐atom molecular dynamics simulations by Hiromi Baba et al., https://doi.org/10.1002/jcc.26975